TASYRȊḤ AL JATSTSAT (AUTOPSI): Fungsi dan Urgensinya dalam Kedokteran Perspektif Hukum Islam - Herfin Fahri; Vita Fitriatul Ulya (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2021)
This article discusses the autopsi (tasyri>h al Jatsts) in the perspective Islamic law. In this modern era, autopsies are an alternative choice for the medical and police to resolve a criminal case. So there needs to be a discussion regarding how the scholars of jurisprudence punish the autopsy. This study uses a qualitative research type with a literature review approach. Researchers conduct studies and analyzes of various literatures relevant to the topic to obtain information. Through this literature review, it was found that there were ikhtilaf from fiqh scholars in judging autopsies. Some scholars do not allow forensic autopsies because they can damage the corpse and violate the honor of the corpse. However, some other scholars allow forensic autopsies on the grounds of realizing the benefit of the ummah (mashalih mursalah). Tasyri>h al Jatstsat or autopsies are allowed if they have aclear and good purpose, such as for educational purposes (anatomical autopsies), for scientific purposes (clinical autopsies), and for justice (forensic autopsies). Anatomical autopsies are needed by medical or other health students in order to study anatomy or parts of the human body. A clinical autopsy is needed by a doctor to observe a case of a disease suffered by a patient who dies for the development of medical science. And a forensic autopsy is needed to help law enforcement officers or the police to determine the cause of someone's death that involves a crime. Dissection of forensic corpses is allowed to establish the law fairly as stated in (QS. An-Nisa [4]: 58) that we as Muslims are encouraged to set the law between humans fairly. An autopsy is not justified by religious law if there is no emergency cause, does not cause benefit and is not accompanied by permission from the heirs.